Power Grid Protection: Quantitative Engineering of Dependability, Security, and Cascading Risk Under Modern Operating Conditions - Sokha Chan Sokha Chan; Sophea Chea Sophea Chea; Dara Heng Dara Heng (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents an applied engineering framework for quantifying protection reliability in terms of misoperation risk, failure-to-trip risk, and their downstream consequences for unserved energy and cascading probability. The framework models protection as a decision pipeline in which measurement uncertainty, logic design, communications, and human governance jointly determine outcomes, and it evaluates strategies using metrics meaningful for utility operations: probability of correct operation, misoperation rate, mean time to recovery, expected unserved energy, and risk-weighted outage impact. A generic transmission-and-distribution boundary case is developed with representative line, transformer, and bus protection functions, and scenario-driven quantitative results are provided for instrument transformer saturation events, evolving fault current conditions under high inverter penetration, communication-aided scheme degradation, and settings lifecycle errors. Results indicate that many of the most consequential reliability improvements arise from governance and verification pathways, particularly settings validation, event-driven self-monitoring, and staged fallback logic, rather than from incremental relay hardware upgrades alone. The paper concludes with implementation guidance for condition-based maintenance, alarm and event triage, and risk-based testing intervals, and it provides copy-ready tables and scientific figure prompts suitable for Techne submissions and operational reporting.